USE OF GAME METHODS IN TEACHING SIMULTANEOUS INTERPRETATION - Qadirova Xushnudakhon Azamjon qizi (Bright Mind Publishing, 2025)
This article analyzes the use of game-based methods in teaching simultaneous interpretation and examines their effectiveness in improving students’ knowledge and skills. The results were reviewed based on an experiment conducted over the course of one semester with first-year students of ASIFL (Andizhan state institute of foreign language). During this process, the methods of “Role play”, “Find the story”, “Umbrella”, “Chain translation”, “Pair work”, and “Translation Race” were applied. As a result, students’ motivation increased, vocabulary expanded, and translation errors decreased. The article highlights theoretical foundations, methodological approaches, and empirical analysis.
Keywords: Simultaneous interpretation, game-based methods, collaboration, educational innovations, translation studies, motivation, communicativeness, terminology, vocabulary.